Melanoma survivors are at increased risk for second primary keratinocyte carcinoma. (21st June 2022) - Sun, Huiyan; Li, Yayun; Zeng, Furong; Meng, Yu; Du, Songtao; Deng, Guangtong
Abstract: Background: Recent large cohorts have reported that melanoma survivors are at risk of developing second keratinocyte carcinoma (KC). However, the detailed proportion and risk are still unknown. We aimed to comprehensively analyze the risk of developing keratinocyte carcinoma after primary melanoma. Methods: We conducted systematic literature research in PubMed, Embase, Web of Science, and Cochrane Library published prior to September 13, 2021. Proportion and standardized incidence ratios (SIR) with its corresponding 95% confidence interval (CI) were pooled for assessing the risk. Results: A total of 15 studies encompassing 168, 286 patients were included in our analysis. The pooled proportions of melanoma survivors that developed a subsequent basal cell carcinoma (BCC), squamous cell carcinoma (SCC), and KC were 4.11% (95% CI, 1.32–6.90), 2.54% (95% CI, 1.78–3.31), and 5.45% (95% CI, 3.06–7.84), respectively. The risks of developing a second BCC, SCC, and KC in melanoma survivors were 5.3‐fold (SIR 5.30; 95% CI, 4.87–5.77), 2.6‐fold (SIR 2.58; 95% CI, 1.33–5.04), and 6.2‐fold (SIR 6.17; 95% CI, 3.66–10.39) increased in comparison with the general population. Both fixed effects and random effects models were applied in conducting meta‐analysis and reached a consistent conclusion. Conclusions: Our results indicated melanoma survivors are at elevated risk of experiencing second primary BCC and SCC, which suggested the significance of surveillance for second primary KC and efforts for prevention in patients with a history of melanoma.